Free Glutamate Intake from Foods Among Adults: Case Study in Bogor and Jakarta - Lilis Nuraida; Siti Madaniyah; Nuri Andarwulan; Dodik Briawan; Hanifah Nuryani Lioe; Zulaikhah Zulaikhah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Monosodium glutamate (MSG) is a flavor enhancer which has been used for nearly a century to bring out the best avor of food. Its principal component is an amino acid called glutamate or L-glutamic acid. Free glutamate also exists naturally in foods. The aim of the present study was to estimate the exposure of consumers to free glutamates from foods in Jakarta and Bogor, Indonesia. The study was conducted in Jakarta urban area and rural area of Bogor with 222 respondents above 19 years of age. The survey used Food Frequency Questionnaire to estimate the consumption of food predicted to contain free glutamate. The data of food consumption was used to design food samples to be taken from the survey site and analyze for free glutamate content. Analyses of free glutamate content in food were conducted using HPLC with fluorescent detector. The results revealed the most frequent and the highest amount of food consumed both in Jakarta and Bogor area was dish menus of cereal categories. The average food consumption, excluding rice, in Bogor was 816.73 g/cap/day, while in Jakarta was 823.82 g/cap/day with dish menus contribution accounted to more than 70%. Free glutamate content of food samples ranged from undetected to more than 6 mg/g. Free glutamate intake in Bogor was comparable with that of Jakarta, i.e. 2013.76 mg/cap/day and 2068.97 mg/cap/day respectively. The main source of glutamate intake in both in Bogor and Jakarta was dish menus contributing to more than 80% of the total free glutamate intake. Free glutamate intake from food prepared outside the household was comparable with that of food prepared at home.